Analisis Faktor-Faktor Yang Berhubungan Dengan Stres Kerja Pada Pegawai Rumah Sakit Mata Provinsi Sulawesi Utara - Esra Margaret Singal; Aaltje Ellen Manampiring; Jeini Ester Nelwan (Sam Ratulangi Journal of Public Health, 2020)
Background: Job stress is a very disruptive thing to work. Work-induced stress in particular results in a decrease in work productivity, such as low worker performance, increased absenteeism, decreased work morale, increased worker turnover which can cause the loss of a lot of working time causing the cost of compensation for workers to increase in capital. The purpose of this study was to analyze the factors associated with work stress on the employees of the Eye Hospital of North Sulawesi Province. Methode: This study was an observational study with a cross sectional study design. The population in this study were all employees of the Eye Hospital of North Sulawesi Province. The sample in this study was a total population of 70 employees. The variables in this study were age, marital status, income, years of service and work load, with the dependent variable being work stress. The research data were analyzed using univariate, bivariate and multivariate analysis and chi-square statistical calculations. Presentation of data is made in table and narrative form. Result: The results showed that there was a significant relationship between age and work stress with p value = 0.031, there was a significant relationship between tenure and work stress with a value of p = 0.004, there was a significant relationship between workload and work stress with p = 0.003, there is no significant relationship between marital status and work stress with a value of p = 0.077 and there is no significant relationship between income and work stress with a value of p = 0.473. The result of multivariate analysis showed that workload (p = 0.002; OR = 21.667) was the most dominant factor affecting work stress on the employees of the Eye Hospital of North Sulawesi Province. Conclusion: The conclusion of this study is that age, years of service and workload are factors that are associated with work stress. The most dominant factor affecting employee work stress is workload.